Cognitive interviewing to improve women's empowerment questions in surveys: Application to the health and nutrition and intrahousehold relationships modules for the project‐level Women's Empowerment in Agriculture Index. Issue 1 (14th August 2019) - Hannan, Anika; Heckert, Jessica; James‐Hawkins, Laurie; Yount, Kathryn M.
Abstract: In 2015, the United Nations adopted the Sustainable Development Goals, which include fostering gender equality and women's empowerment and ending hunger and malnutrition. To monitor progress and evaluate programmes that aim to achieve these goals, survey instruments are needed that can accurately assess related indicators. The project‐level Women's Empowerment in Agriculture Index (pro‐WEAI) is being developed to address the need for an instrument that is sensitive to changes in empowerment over the duration of an intervention. The pro‐WEAI includes new modules with previously untested survey questions, including a health and nutrition module (focused on women's agency in this area) and an intrahousehold relationships module. This study uses cognitive interviewing to identify how new survey questions might be misinterpreted and to understand what experiences women are referencing when they respond to these questions. This was undertaken with the goal of informing revision to the modules. The study was conducted in Bangladesh with women from nuclear, extended, and migrant‐sending households and from two regions of the country to identify difficulties with interpretation and response formulation across these groups. Findings revealed that questions were generally understood, but participants occasionally responded to the wrong part of the question, did not understand key phrases, or were uncomfortable with questions. The findings also suggested ways to revise the modules and strengthen the pro‐WEAI. The revised pro‐WEAI health and nutrition and intrahousehold relationships modules will advance the ability to measure changes in these domains and their relationship with the health and nutritional status of women and their children.